Hologram Technology as the Future of Islamic Learning: A Bibliometric Analysis - Muhammad Buya Al-Madany Abror; Nadisah Khairani Nasution; Nur Qamarina Kamari; Anita Ekantini; Muhammad Hidayat; Muhammad Affan Ramadhan (EDUKASIA, 2026)
The rapid advancement of digital technologies has transformed educational practices worldwide; however, Islamic religious education, particularly Fiqh instruction, continues to face challenges in conveying abstract concepts through conventional teaching approaches. This study examines research trends in the implementation of holographic technology in Islamic education and investigates its potential for supporting integrative learning. A bibliometric analysis was conducted on 655 documents indexed in Scopus between 1981 and 2026 using the keywords “Technology,” “Hologram,” “Islamic Learning,” “Education,” and “Learning.” The data were analyzed using VOSviewer to identify publication trends, thematic developments, and collaboration patterns. The findings reveal increasing scholarly interest in hologram-based Islamic religious education, with “Technology,” “E-Learning,” “Islamic Education,” and “Hologram” emerging as the most prominent keywords. The convergence of these themes highlights the potential of integrative learning approaches that combine Islamic religious instruction with digital innovations to enhance student engagement, conceptual understanding, and learning outcomes. Despite this growing interest, the research landscape remains limited and fragmented, suggesting that the field is still in an early stage of development and requires further investigation to establish robust pedagogical frameworks and implementation strategies. A key limitation of this study is its exclusive reliance on the Scopus database, which may exclude relevant publications indexed elsewhere and consequently limit the comprehensiveness of the bibliometric mapping.